2y+7=-2y-1

Simple and best practice solution for 2y+7=-2y-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2y+7=-2y-1 equation:


Simplifying
2y + 7 = -2y + -1

Reorder the terms:
7 + 2y = -2y + -1

Reorder the terms:
7 + 2y = -1 + -2y

Solving
7 + 2y = -1 + -2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '2y' to each side of the equation.
7 + 2y + 2y = -1 + -2y + 2y

Combine like terms: 2y + 2y = 4y
7 + 4y = -1 + -2y + 2y

Combine like terms: -2y + 2y = 0
7 + 4y = -1 + 0
7 + 4y = -1

Add '-7' to each side of the equation.
7 + -7 + 4y = -1 + -7

Combine like terms: 7 + -7 = 0
0 + 4y = -1 + -7
4y = -1 + -7

Combine like terms: -1 + -7 = -8
4y = -8

Divide each side by '4'.
y = -2

Simplifying
y = -2

See similar equations:

| 4/9/x=12 | | (2x+3y-4)dx+(-4x+y+1)dx=0 | | 7x-3.5=-4x-3.2 | | 2-2x=6-1x | | 5/9÷15/36 | | x^5-125x^3+484x=0 | | 20-8.50= | | x^2-2mx+8m=0 | | 27=6+3y | | -10=u/5-5 | | x(5x^2-15x-1)=3 | | X+6x=100 | | 6a+4b-5a-b+3= | | (x^2)/3=7/2 | | x^2/3=7/2 | | 9(x+11)=-6(x-20) | | 3(a+2)+4(a+5)= | | -k-3+k^3-3k^2=0 | | (x-1)/4-3=(x-7)/3 | | 25=625-50x | | -9u+7=24u-4 | | P(x)=x^3-25x+12 | | 4a+b+3a+2b= | | (2x+y)dx+(x+y+1)dy=0 | | 17-3z=z-1 | | 5p=5p-15 | | 980n=361 | | 308-11x=8x | | 575980x=130361 | | 575980x=361 | | 8/3x=-16/3 | | =361 |

Equations solver categories